KUALITAS LAYANAN DAN KEPUASAN NASABAH PADA PT. ARMADA FINANCE DI SAMARINDA - Anwar, Hairil (EKONOMIA, 2013)
This studyaims to determinehow the effect ofservice qualityon customer satisfactionwithPT. ArmadaFinanceinSamarinda, as well astodetermine which variableshavethe servicesmost impact oncustomersatisfactionatPT. ArmadaFinanceinSamarinda.Analysis toolsto be usedin the studyisStatisticsLinear Regressionandassistedby usingSPSSversion19.0computercalculations. The variablesincluded inthis studyis theindependent variable(X) consistingofReliability(X1), Responsiveness(X2), Assurance(X3), Emphaty(X4) andTangibles(X5) and thedependent variable(Y) iscustomersatisfaction, withthe number of samplesthat will be therespondents in this studyas many as88people.Ofcalculationandanalysis, it can be seenthat thevariableReliability(X1), Responsiveness(X2), Assurance(X3), Emphaty(X4) andTangibles(X5) has a significant influenceon customer satisfaction. This was confirmedalsobythe value ofF count=19.039at significance levelÎ±=0.000is greater thantheF table=2.311at significant levelÎ±=0.05for 82degrees of freedom. The mostinfluentialindependent variableon the dependent variable(customer satisfaction) isAssurancevariablewith avalue oft =3.585>from thetable =1.661andT=0.001Sig.From theresults of these calculationsso thatit can be concludedthat thevariableReliability(X1), Responsiveness(X2), Assurance(X3), Emphaty(X4) andTangibles(X5) have asignificant influence oncustomersatisfactionin thePT. ArmadaFinanceinSamarinda, as well asAssurancevariablehas thegreatest influenceon customer satisfactionin thePT. ArmadaFinanceinSamarinda.